Obesity (IntechOpen, 2026)
Obesity - Current Science and Clinical Approaches offers a comprehensive exploration of innovative and holistic approaches to understanding and managing obesity. This volume investigates the multifaceted nature of obesity, addressing its impact across different age groups and presenting the latest treatments and interventions. By focusing on integrative strategies, the book highlights the importance of interdisciplinary collaboration, lifestyle modifications, and advanced therapeutic techniques. Readers will gain valuable insights into the latest research and practical applications, making this an essential resource for healthcare professionals, researchers, and anyone committed to combating obesity. With its emphasis on integrative and new perspectives, this book provides a unique and thorough understanding of obesity management, promoting better health outcomes and improved quality of life.